Pre-eruptive excess volatiles and their relationship to effusive and explosive eruption styles in semi-plugged volcanoes - Utami, Sri Budhi (2023)
Understanding the role of various factors influencing eruption style is challenging, but it can aid in adapting different hazard mitigations and crisis responses for explosive or effusive events. Here, we focus on the role of magma storage conditions in controlling eruption styles at basaltic andesite volcanoes, and how they can be related to monitoring data. We study the cycle of explosive (1990, sub-Plinian) → effusive (2007, dome) → explosive (2014, sub-Plinian) eruptions from Kelud (Kelut) volcano, Indonesia. We conducted petrological analyses of the eruption products and phase equilibria experiments using pumice and explored a range of temperatures, pressures, oxygen fugacity, and volatile contents. We show that we can reproduce the main mineral assemblage (plagioclase ± pyroxenes ± magnetite ± amphibole ± olivine) and phenocryst content (30–50 wt%) of the magmas from the three eruptions at T = 975 ± 39°C, p = 175 ± 25 MPa, fO2 = nickel–nickel oxide buffer, and about 4–6 wt% water in the melt (ca. 3 to 5 wt% and ca. 4 to 7 wt% for the 1990 and 2014 eruptions, respectively). However, geothermobarometric results also indicate that some crystals of amphibole were sourced from higher pressures. We infer from a synthesis of our data and historical observations that the high phenocryst content of the 2007 dome (∼70 wt%) likely resulted from slow magma ascent toward the surface alongside progressive degassing and re-equilibration at a lower volatile content (∼1 wt% water in the melt). Mass balance calculations on the sulfur budget of the 1990, 2007, and 2014 magmas show that the explosive events contained an excess fluid phase at pre-eruptive conditions, and we propose that this led to their higher explosivity compared to the 2007 dome. The accumulation of excess fluids during decadal-long repose depends on how plugged the volcanic system is, or its ability to passively release magmatic fluids, prior to eruption. Such condition could be inferred from monitoring records, including changes in gravity of the plumbing system over time, and thus contribute to better anticipate eruptive style.